2012
DOI: 10.1136/neurintsurg-2012-010314
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular geometry in the anterior circulation: an analysis of diameter, length and the vessel taper

Abstract: ICA and MCA vessel size did not change based on gender or side. Older patients had more redundant vessels based on diameter and length. The ICA has a gentle taper from its proximal cavernous segment to the ICA terminus. This information can be important in planning interventions or designing endovascular devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 19 publications
2
68
2
Order By: Relevance
“…Wollschlaeger et al (37) reported angiographic measurements of 2.03 mm for ACA, 2.87 mm for MCA and 3.7 mm for ICA. A recent study on cerebrovascular geometry in the anterior circulation reported mean diameter of 5 ± 0.6 mm and 3.6 ± 0.4 mm for cavernous ICA and the ICA terminus measured with computed tomography angiography (28). They also reported mean diameters of 3.1 ± 0.4 mm and 2.4 ± 0 mm at the MCA and M2 origins respectively.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Wollschlaeger et al (37) reported angiographic measurements of 2.03 mm for ACA, 2.87 mm for MCA and 3.7 mm for ICA. A recent study on cerebrovascular geometry in the anterior circulation reported mean diameter of 5 ± 0.6 mm and 3.6 ± 0.4 mm for cavernous ICA and the ICA terminus measured with computed tomography angiography (28). They also reported mean diameters of 3.1 ± 0.4 mm and 2.4 ± 0 mm at the MCA and M2 origins respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Knowledge of cerebrovascular dimensions is crucial for the performance of neurovascular procedures (28). Angiographic normative data about the diameters of cerebral arteries in adults is reported in detail in the literature (19,24,28,32,34) with endovascular instruments such as stents being manufactured based on these measurements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, clots with lower HU were less likely to recanalize compared to clots with higher HU [14,15] Problems with detection of the hyperdense artery sign include false positives and false negatives. The average width of the middle cerebral artery (MCA; the most common site of occlusion in AIS) is 3-4 mm [16]. Scans that [10] exceed this width and are of average signal may potentially miss detecting the hyperdense sign because of the phenomenon of partial volume averaging.…”
Section: Clot Densitymentioning
confidence: 99%